Extension and Dynamics of the Andes Inferred From the 2016 Parina (Huarichancara) Earthquake - Wimpenny, Sam (2018)
[EN] The Mw 6.1 2016 Parina earthquake led to extension of the south Peruvian Andes along a normal fault with evidence of Holocene slip. We use interferometric synthetic aperture radar, seismology, and field mapping to determine a source model for this event and show that extension at Parina is oriented NE‐SW, which is parallel to the shortening direction in the adjacent sub‐Andean lowlands. In addition, we use earthquake source models and GPS data to demonstrate that shortening within the sub‐Andes is parallel to topographic gradients. Both observations imply that forces resulting from spatial variations in gravitational potential energy are important in controlling the geometry of the deformation in the Andes. We calculate the horizontal forces per unit length acting between the Andes and South America due to these potential energy contrasts to be 4–8 ×1012 N/m along strike of the mountain range. Normal faulting at Parina implies that the Andes in south Peru have reached the maximum elevation that can be supported by the forces transmitted across the adjacent foreland, which requires that the foreland faults have an effective coefficient of friction ≤ 0.2. Additionally, the onset of extension in parts of the central Andes following orogen‐wide compression in the late Miocene suggests that there has been a change in the force balance within the mountains. We propose that shortening on weak detachment faults within the Andean foreland since ∼5–9 Ma reduced the shear tractions acting along the base of the upper crust in the eastern Andes, leading to extension in the highest parts of the range.